맹자의 소통원리와 방법론 - 이권영; Kwon Young Lee (孔子學, 0(18), 2010)
이 논문은 맹자의 시대적 배경과 정치 커뮤니케이션의 기본사상과 소통 소통원리와 방법론을 규명했다. 당시의 시대적배경은 첫째 춘추전국시대 호족(귀족)들의 약소 씨족에 대한 병합 전쟁상황이었다. 둘째, 귀족정치의 초기적 발흥기로서 이기적 부국강병주의 시대였다. 셋째, 폐도정치와 상호공벌주의 시대였다. 넷째, 이익추구의 절대주의시대였다. 맹자의 정치적 설득소통의 기본 사상은 대체로 다음과 같이 요약할 수 있다. 첫째, 맹자는 인의예지를 중심으로 여민정치와 여민동락의 위민정치를 추구하였다. 둘째, 민본주의이다. 인의를 통해 여민동락을 권고하고 백성인민을 위한 정치를 강조했다. 셋째, 천명사상의 계승자로 성선설을 주창했다. 넷째, 왕도정치의 주창자로서 인의(仁義)의 도덕으로서 인정(仁政)을 주장했다. 끝으로, 비전오살(非戰惡殺)의 평화주의자이다. 맹자의 소통원리는 다음과 같이 제시하고자 한다. 첫째, 인의숭상 이익 배격주의이다. 이익을 추구하면 이익 쟁탈전이 되어 모두가 망한다는 것이다. 반면, 인의를 추구하는 소통의 설득에서는 태평성대를 누린다. 둘째, 국민 공유주의이다. 민본주의를 토대로 국민공유를 존중하는 소통정신의 표현이다. 국민과 함께 즐거움, 근심도 공유할 때, 성공적인 소통전략이 된다. 셋째, 국민여론주의이다. 인재의 등용과 처벌제도는 국민전체여론의 결정에 따르고, 천하를 얻기 위한 정치적 소통의 설득원리도 국민 여론의 반영이다. 결론적으로 맹자의 3대 소통적 설득원리의 관계적 특징은 다음과 같다. 인의숭상 이익배격주의는 국민공유주의와 국민여론주의와의 상호보완적 관계이다. 전자가 근본원리로서 설득과 소통의 원리라면, 후자는 이 원리를 토대로 구체적 방법원리로 활용된 사례이다. 즉 국민을 사랑하고 올바른 길로 인도하는 원리가 국민공유주의와 국민여론주의를 통한 대국민의 현실적 정치문제해결의 원리를 제공한다고 평가할 수 있다. 그의 소통의 설득정신은 인의를 근거로 한 민본주의로 해석할 수 있다. 나아가 이는 국민생활을 위한 왕도주의의 실현을 위한 소통의 설득원리로 작용할 것이다. 맹자의 소통 방법론은 성선설의 인간 존중 소통법, 자아 커뮤니케이션 소통법, 공감적 공유 소통법으로 분류, 제시되었다. 맹자는 인과 더불어 정의를 강조함으로써 토론에서도 공격적이며 토론자를 공격하는 논리를 구성하고 있다. 논리 전개법은 점증법과 극단적 2분법적 대조법을 토대로 역사적이며 경험적 사실에 근거한 논증법이다. 나아가 유추적 논리로 일반화를 시도하고 있다. This Study is concernded with the communication principles and methodologies in the work of Mencius. The communication principles in the work of Mencius are followings. First, theory of a benevolence(ren: 仁) and righteousness(yi: 義) against a profit is a powerful persuasive factor in communicating with people, on the base of Mencius’s claim that ren and yi is in a human nature. He defines that profit is bad in a sense that people fight for more profits without satisfacting with it, while ren and yi is good in a sense that ren and yi contributes to the successfull relations between King and people, younger and older brother, and, parants and their sons. Therefore, the Factors of ren and yi has a very persuasive power in communicate with people. Second, theory of the people’s shareness with King in both enjoying and worrying has a powerful persuasive factor in communicating with them, on the base of Mencius’s belief that the people is the most important element in a nation. Third, theory of people's public opinion has a very powerful factor in communicating with people to treat their national affaires, on the base of Mencius’s belief that the people is the most important element in a nation. The communication methodologies in the work of Mencius are followings. First, theory of a good human nature is a respecting factor for human beings in communicating with people, on the base that the human beings is born good naturally in a sense that all people has ren and yi in themselves . Second, theory of self-communication is a powerful factor in completing of a moral man with ren and yi. The theory is a mind practice proccess. Third, theory of empathic shareness communication is a powerful factor in communicating with people, their friends and nations. KCI Citation Count: 1